Dehydration-driven stress transfer triggers intermediate-depth earthquakes - Thomas P. Ferrand (Nature Portfolio, 2017)
Intermediate-depth earthquakes (30-300 km) occur in subducting oceanic slabs, but their generation mechanism remains enigmatic. Here, the authors show through high-pressure and dehydration experiments of antigorite that dehydration-driven stress transfer triggers intermediate-depth earthquakes.